Heart Failure Nurses within the Primary Care Setting - Loreena Hill; Anne McNulty; James McMahon; Gary Mitchell; Cathy Farrell; Izabella Uchmanowicz; Teresa Castiello (Cardiac Failure Review)
Cardiology services within primary care often focus on disease prevention, early identification of illness and prompt referral for diagnosis and specialist treatment. Due to advances in pharmaceuticals, implantable cardiac devices and surgical interventions, individuals with heart failure are living longer, which can place a significant strain on global healthcare resources. Heart failure nurses in a primary care setting offer a wealth of clinical knowledge and expertise across all phases of the heart failure trajectory and are able to support patients, family members and other community services, including general practitioners. This review examines the recently published evidence on the current and potential future practice of heart failure nurses within primary care.